A Comparison of Quantitative and Qualitative Methods to Measure Wildlife Value Orientations Among Diverse Audiences: A Case Study of Latinos in the American Southwest. Issue 5 (3rd May 2016) - Chase, Loren D.; Teel, Tara L.; Thornton-Chase, M. Rebecca; Manfredo, Michael J.
ABSTRACT: As American society diversifies, and the public interest in natural resources broadens, it is essential that wildlife agencies find ways to better understand and engage increasingly diverse audiences. Wildlife value orientations (WVO) is a concept that addresses this need by augmenting understanding of the different ways people perceive wildlife resources. However, as agencies apply this concept within diverse audiences, it raises questions about the potential limitations of traditional survey methods for WVO assessment across cultures. To address this gap, we examined WVOs in Latino communities in the southwestern United States using four methods: survey, self-identification, qualitative interviews surrounding stories about wildlife, and another interview regarding images of wildlife. We found the four methods measured WVOs with moderate to strong correlations, confirming they may be beneficial for measurement within Latino communities and in broader cross-cultural contexts. Because different methods offer advantages in different research settings, we identify scenarios wherein each method may be beneficial.